An alternative start regimen with aripiprazole once-monthly in patients with schizophrenia: population pharmacokinetic analysis of a single-day, two-injection start with gluteal and/or deltoid intramuscular injection. (2nd November 2021) - Wang, Yanlin; Wang, Xiaofeng; Harlin, Matt; Larsen, Frank; Panni, Moeen; Yildirim, Murat; Madera, Jessica; Arias, Liz; Forbes, Andy; Mustafa, Nihal; Ruiz-White, Inez; Raoufinia, Arash
Abstract: Background: The single-injection start regimen for aripiprazole once-monthly 400 mg (AOM 400) in patients with schizophrenia requires a single intramuscular injection in the gluteal or deltoid site and 14 days of concurrent oral therapy. A simplified, single-day regimen of two injections at separate gluteal and/or deltoid injection sites, together with a single 20-mg dose of oral aripiprazole on the 1st day, was assessed. Patients and methods: A previously developed population-pharmacokinetic (popPK) model for characterizing aripiprazole PK following oral administration and gluteal intramuscular depot injection was expanded to include deltoid injection. Simulations were conducted to assess PK profiles following various (including two-injection) start regimens. Postmarketing data on patients who received higher-than-recommended AOM doses were used to assess overall safety/tolerability. Results: The two-injection start regimen with a single concurrent oral dose displayed a comparable PK profile to the single-injection start regimen with concurrent 14-day oral administration in simulations. The safety assessment indicated the two-injection start regimen was unlikely to be associated with safety concerns beyond those expected with a single-injection start regimen. Conclusion: These data support use of the two-injection start regimen in clinical practice to reduce reliance on daily oral administration and optimize the therapeutic benefits of AOM 400 in patients with schizophrenia.